1999
DOI: 10.1007/s11626-999-0113-6
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of 13 cell lines from a green turtle (Chelonia mydas) with fibropapillomas

Abstract: SUMMARYThirteen cell lines were established and characterized from brain, kidney, lung, spleen, heart, liver, gall bladder, urinary bladder, pancreas, testis, skin, and periorbital and tumor tissues of an immature male green turtle (Chelonia mydas) with fibropapillomas. Cell lines were optimally maintained at 30 ° C in RPMI 1640 medium supplemented with 10% fetal bovine serum. Propagation of the turtle cell lines was serum dependent, and plating efficiencies ranged from 13 to 37%. The cell lines, which have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 18 publications
2
46
0
Order By: Relevance
“…This method was adapted accordingly from previous cell line establishment efforts (Lu et al 1999, Zhao & Lu 2006. Each cell line was originally seeded in 25 cm 2 tissue culture flasks and later passed into 75 cm 2 tissue culture flasks for cultivation (Corning Life Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…This method was adapted accordingly from previous cell line establishment efforts (Lu et al 1999, Zhao & Lu 2006. Each cell line was originally seeded in 25 cm 2 tissue culture flasks and later passed into 75 cm 2 tissue culture flasks for cultivation (Corning Life Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…At 37°C however, the cells were noticeably ragged and granulated, resulting from acceleration of metabolism by rapid change in pH. Lu et al (1999) also reported that cells from C. mydas with fibropapillomas, exhibited optimal growth at 30°C and were able to proliferate at incubation temperatures between 20 and 25°C. However cell growth was not observed when cultures were incubated at 37°C or 15°C.…”
Section: Discussionmentioning
confidence: 88%
“…These include various cells from the heart of the box turtle, Terrapene carolina (Clark and Karzon, 1967;Huang and Clark, 1967), the skin of the green sea turtle, Chelonia mydas (Koment and Haines, 1982), the heart and lung of the Tokai gecko, Gecko gecko, the heart, liver and kidney of the green iguana, Iguana iguana, the heart of the side-necked turtle, Podocnemis unifilis, and the spleen of the Grecian tortoise, Testudo graeca (Clark et al, 1970). Cell lines have also been established from cutaneous fibropapillomas of C. mydas (Mansell et al, 1989;Lu et al, 1999). However, embryonic cell cultures have not been established from the hawksbill sea turtle, Eretmochelys imbrica.…”
Section: Introductionmentioning
confidence: 99%
“…To initiate primary cell culture, 1 to 2 g of the following tissues were aseptically collected from the fish into antibiotic-incubation medium (AIM): heart, spleen, muscle (under mouth), snout, kidney and swim bladder. Tissue samples were incubated at room temperature (25 ± 2°C) for 2 h in AIM consisting of 1 × Leibovitz medium (L-15), 1000 µg ml -1 streptomycin, 1000 U ml -1 penicillin, 25 µg ml ), according to previously described methods (Lu et al 1999), and incubated at 25°C. When cells grew and became confluent, cells were subcultivated at a ratio of 1:2-3 every 5 to 7 d using a 0.25% trypsinversene solution (Sigma Chemical).…”
Section: Methodsmentioning
confidence: 99%
“…A large number of cell lines have been established from a variety of marine species, including aquacultured fish (Wolf & Mann 1980, Fijan et al 1983, Lannan et al 1984, Chen & Kou 1988, Lu et al 1990, Fryer & Lannan 1994) marine mammals (Kadoi et al 1992, Lu et al 1998, Kumar et al 2001, endangered marine species (Moore et al 1997, Lu et al 1999, and marine crustaceans , Neuman et al 2000. However, for Caranx species, there has only been one report of the establishment of an in vitro cell culture derived from omaka Caranx mate fish larvae (Lee & Loh 1975 Table 1 for definitions of virus abbreviations is an urgent need to gain a biological understanding of this fish, and to develop a biological tool for the detection and diagnosis of infectious viruses which affect it.…”
mentioning
confidence: 99%